Posouzení informačního systému firmy a návrh změn - Brodňanský, Erik (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2022)
The diploma thesis focuses on the assessment of the information system, which is used to record the hours worked, in a specific company. In addition to the assessment of the system itself, it also deals with the proposal for its change, the implementation procedure, together with the risk management and time analysis. The content of the work is, in addition to the above, the analysis of the company in terms of external and internal environment, a description of the information systems used and their audit.
Keywords: company analysis; Zefis; information systems; Lewin's model of change; McKinsey 7S; SLEPTE; risk management; API; Porter's five forces framework; PERT; SWOT